The medical demands of the special athlete - Batts, K. B.; Glorioso, J. E.; Williams, M. S. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: To identify the most common injuries and medical conditions experienced by the mentally handicapped athlete during Special Olympic competition. DESIGN: A longitudinal, observational, and prospective study. SETTING: Hawaii Special Olympic Summer Games, 1993-1996. PARTICIPANTS: A total of 2326 athletic participants were registered during a 4-year period in the Hawaii Special Olympic Summer Games. The athletes ranged in age from 8 to 76 years. INTERVENTION: Medical encounter forms were documented by physicians and nurses on participants treated at aid stations located at the athletic venues and Olympic village during competition. MAIN OUTCOME MEASURES: The number and type of injuries and medical conditions encountered during Special Olympic competition were recorded on standard medical forms supplied by the U.S. Special Olympic Committee. RESULTS: Ninety athletes (3.87%) required medical attention during four annual Special Olympic Summer Games. A total of 52 (57.8%) injuries and 38 (42.2%) medical conditions were reported during the 4 years. Of the 90 encounters, 86.7% (n = 78) were acute and 13.3% (n = 12) were nonacute medical problems. More than 61% (n = 55) of the injuries and medical conditions occurred during actual competition. The majority of injuries occurred during track and field events (n = 25, 56%), and the most commonly injured site was the knee. CONCLUSIONS: Despite preexisting medical conditions and physical limitations of the Special Olympian, most of the medical demands encountered during athletic competition are acute, minor injuries. No athlete sustained more than one injury during the period studied.